Saliva acid phosphatases in Malaysians: report of a new variant - Tan, Soon Guan; Teng, Yao Sheng (Karger, 1979)
A total of 640 Malaysians, 355 of Malay, 155 of Chinese, and 130 of Indian ancestries have been examined for saliva acid phosphatases. The three ethnic groups were polymorphic for saliva acid phosphatase A (Sap-A) and saliva acid phosphatase (B (Sap-B). The gene frequencies were: Sap-A, Malays: A = 0.469, A' = 0.001, A degrees = 0.530; Chinese: A = 0.436, A' = 0.010, A degrees = 0.555; Indians: A = 0.533, A' = 0.012, A degrees = 0.456. For Sap-B, Malays: B = 0.925, B degrees = 0.075; Chinese: B = 0.797, B1 = 0.016, B degrees = 0.187; Indians: B 0.752, B degrees = 0.248. Phenotype ABB1 is described.